Nationwide frequency, risk and outcomes of type-2 myocardial infarction in patients with versus without previously revascularized myocardial infarction (type 1). (11th May 2022) - Desai, R; Mandal, A; Peethala, MM; Raju, AR; Fatima, B; Valdez-Aquino, C; Raina, J; Itare, V; Mishra, V; Jain, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Type 2 myocardial infarction (T2MI), due to a mismatch between myocardial oxygen demand and supply, is being increasingly recognized with improved diagnostics. The upsetting concern of developing T2MI in patients with prior revascularized occlusive acute myocardial infarction (AMI) or type 1 MI (T1MI) makes it crucial to define the clinical profile and outcomes of T2MI in revascularized patients of ACS. Purpose: To determine the risk and prognosis of T2MI in patients who had previously had coronary revascularization (PCI or CABG) Methods: We used the National Inpatient Sample (2018) dataset from the United States to identify T2MI adult hospitalizations using ICD-10 codes and define our study arm as T2MI excluding secondary T1MI diagnoses but having prior revascularized (with percutaneous coronary intervention or coronary artery bypass grafting) AMI. We then compared demographics and comorbidities in T2MI cohort with vs without personal history of revascularized AMI. We used multivariate analysis to study the odds of T2MI hospitalizations with prior revascularized AMI and in-hospital outcomes (all-cause mortality, cardiogenic shock and resource utilization) adjusting for confounders. Results: There were 33155 T2MI adult hospitalizations after excluding AMI (median age 71 years, 50.6% male, 67.3% white); 1435 (4.3%) had previously revascularized AMI. T2MI in the study arm had higher chances of hospitalization with prior revascularized AMI when adjusted for socio-demographics (aOR 6.92, 95% CI:6.50-7.36, p<0.001) and socio-demographics with comorbidities (aOR 5.70, 95%CI: 5.48-5.94, p<0.001) (Table 1). Study arm often had elderly (≥65 years old, 78.4% vs 65.8%), male (66.6% vs 49.9%), white (76.7% vs 66.9%), upper socio-economic class (20.2 vs 16.8%), patients who were often admitted to non-electively (99.3 vs 97.1%) and to rural (10.5 vs 9.3%) hospitalizations compared to control arm. The study arm had a significantly higher prevalence of diabetes mellitus, hyperlipidemia, peripheral vascular disease, chronic obstructive pulmonary disease, renal failure, deficiency anemias, prior TIA/stroke, depression and smoking. T2MI cohort with prior revascularized AMI did not show any significant association with in-hospital all-cause mortality (1.7 vs 3.0%, aOR 0.49, 95%CI 0.18-1.34, p=0.164) and cardiogenic shock (1.7% vs 2.1%, p=0.399) however, had lower hospital expenditure (median USD 31273 vs 36567) and fewer transfers to other facilities (19.5 vs 22.1%) than those without prior revascularized AMI (Table 2). Conclusion: Population-based analysis of this nationally representative sample revealed up to six times higher risk of developing T2MI in patients with prior history of AMI (revascularized) but without any significant impact on all-cause in-hospital mortality or cardiogenic shock. Future studies are warranted to assess the short-term/long-term outcomes of T2MI in high risk patient population with previously revascularized AMI.